2023
DOI: 10.3389/fcvm.2023.1161017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal left atrial compliance is associated with a history of life-threatening arrhythmia in corrected Tetralogy of Fallot

Abstract: ObjectivesThe objectives of this study were to examine left atrial (LA) function and compliance using two-dimensional (2D) strain analysis in adult patients with corrected Tetralogy of Fallot (c-ToF) and to investigate the relationships between LA function and patient characteristics, especially history of life-threatening arrhythmia (h-LTA).MethodsFifty-one c-ToF patients (34 males; age, 39 ± 15 years; h-LTA, n = 13) were included in this retrospective monocenter study. In addition to a 2D standard echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Finally, different studies have observed that the mechanics of both the left atrium (LA) and right atrium (RA) are impaired in this population [22][23][24]. In particular, an association has been identified between abnormal left and right atrial compliance and a history of life-threatening arrhythmia in individuals with corrected TOF [23,24].…”
Section: Advanced Echocardiography In Tetralogy Of Fallotmentioning
confidence: 97%
“…Finally, different studies have observed that the mechanics of both the left atrium (LA) and right atrium (RA) are impaired in this population [22][23][24]. In particular, an association has been identified between abnormal left and right atrial compliance and a history of life-threatening arrhythmia in individuals with corrected TOF [23,24].…”
Section: Advanced Echocardiography In Tetralogy Of Fallotmentioning
confidence: 97%